Correlation of Bio-physicochemical Factors with the Expansion of Mangrove Forests in Laikang Bay, Indonesia - Mulyani, Sri; Surya, Batara; Rasyidi, Emil Salim; Muhibuddin, Andi; Mahmud, Haris (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2024)
The bio-physicochemical conditions of seawater are critically important in the rate of expansion of mangrove forests. This study aims to assess the driving factors of mangrove forest expansion with bio-physicochemical water quality analysis using the Maximum Entropy (MaxEnt) method in Laikang Bay, Indonesia. Water quality analysis included measurements of NO3, PO4, kH, salinity, current speed, brightness (D3), NO2, pH, and chlorophyll-a levels (bio-physicochemical factors). This research adopts quantitative methods, with data collected from 42 specific locations between 12:00 a.m. and 3:00 p.m. The observation data was gathered using the stratified random sampling method. Spatial distribution mapping of mangroves and observation data were analyzed using Euclidean nearest neighbor distance with ArcGIS software version 8.1. The MaxEnt method was applied to investigate the percentage contribution of water quality on the distribution of mangroves. The results of this study indicate that the most significant factor contributing to the growth and expansion of mangrove forests in Laikang Bay is the PO4 content, with a contribution value of 47.4%. The PO4 concentration ranges from 0.10 to 1.40 mg.100g-1, with a concentration of approximately 0.10 mg.100g-1 having the greatest impact. Meanwhile, the less influential factor is brightness (D3), with a contribution value of 0.3%. These results indicate that to maintain the growth and expansion of mangrove forests in Laikang Bay, it is necessary to maintain the levels of these influential variables.